Analytical study of bladder tumor - Agrawal, Akash; Kalaswa, Rashmin; Palekar, H. D. (International Surgery Journal, 2018)
Background: Treatment of bladder tumor still provides the romance in Urology. The purpose of this study is to study the prevalence of various types of bladder tumors, to compare various treatment modalities for bladder tumors, to study different presentations of patients with bladder tumor. Methods: The present study was a prospective analytical study of 30 patients of bladder tumor conducted at Dhiraj General Hospital attached to S.B.K.S Medical College from October 2011 to July 2013. All the details of patients in term of demography, risk factors, symptoms and sign, radiological, endoscopic, histopathological features, various treatment modalities offered, and follow-up of patients were studied and analysed using descriptive statistics. Results: Maximum number of patients was presented in sixth decade of life. Youngest patient was 30 years old and oldest patient was 77 years old. 80% patients were male, and 20% patients were female. History of smoking was present in 22 patients, history of exposure to occupational hazards was present in 4 patients and only 2 patients had positive family history. Majority 93.3% patients were presented with haematuria and 16 patients had anaemia. 15 patients had high grade muscle invasive TCC, followed by 10 patients with low grade non-muscle invasive TCC. 3 patients were having low grade non-muscle invasive SCC, 1 patient was having high grade muscle invasive SCC and 1 patient was having high grade non-muscle invasive TCC. Conclusions: The findings of the study conclude that TURBT followed by intravesical instillation of BCG gave good results in patients with low grade and high grade non-muscle invasive tumor. For muscle invasive tumor radical cystectomy with urinary diversion is the ideal treatment but TURBT followed by radiotherapy has also given good results with fewer side effects.